Experimental Study on Friction Sliding Performance of Rubber Bearings in Bridges - Yue Li; Qiqi Wu (Advances in Materials Science and Engineering)
To fully ascertain the ultimate shear failure state and the friction sliding performance of laminated rubber bearings in bridges, a series of cyclic loading tests were conducted. The energy dissipation characteristics of the laminated rubber bearings with two end plates, rubber bearings with unilateral friction sliding, and lead rubber bearing (LRB) under low-frequency cyclic loads were compared and analyzed. The results showed the following. (1) The ultimate shear deformation of the rubber bearings with two end plates could reach 300% to 400% of the rubber layer thickness. The energy dissipation capacity of the bearings was weak, and the hysteresis curves presented narrow zonal shapes. (2) The rubber bearings with unilateral friction sliding had similar energy dissipation capacities compared to the LRB. With the increase of the sliding distance, the dissipated energy continuously enlarged. The shear deformation of the bearing was no longer increased after reaching the maximum. After the test, the bearings remained in a good condition. The hysteresis curves of the load and displacement presented bilinear shapes. (3) Under the cyclic loading, the energy dissipation capacity of LRB was stable. The hysteresis curves of LRB were always fuller than the laminated rubber bearings.